Multiple pathway quantum beat spectroscopy - Yi, Zhenhuan; Begzjav, Tuguldur Kh.; Ariunbold, Gombojav O.; Zheltikov, Aleksei M.; Sokolov, Alexei V.; Scully, Marlan O. (Frontiers in Physics, 2022)
We investigate quantum beats by monitoring cooperative emission from a rubidium vapor, and demonstrate correlated beats via coupled emission channels. We develop a theoretical model and our simulations are in good agreement with experimental results. The results pave the way for advanced techniques measuring interactions between atoms that are exited to high energy levels.